Tenure choice: Fundamentals and a simulation - Bernardo Alves Furtado; Jo\~ao Gabriel de Moraes Souza (Institute for Applied Economic Research (ipea), 2020)
Real estate markets are subject to dynamic, ever-changing influences from location, amenities and neighborhoods; regulation, zoning and population changes; but also - macroeconomic variables, such as interest rates, inflation and economic cycles. The decision to buy or rent a durable, financially significant asset is a difficult one for both experts and amateurs alike. This paper provides a review of classic urban economic fundamentals and a more recent financial and macroeconomic analysis of the literature. There is consensus that a complex, long-term number of factors apply to the market and no single model can encompass all uncertainties revolving around the decision-making. Aiming at offering a practical tool, we propose a numerical simulation that takes the parameter space of renting versus purchasing homes to probabilistic estimate which choice would be more advantageous, more often. We analyze four concrete cases using Brazilian market sensible parameters. The simulation suggests that the amortization scheme known as SAC for the mortgage system is a better choice in nearly two-thirds of the cases. Renting is preferential on very low relative prices, very high real return or inflation. This pathway - from existing model and literature to a reasonable space of advantageous choice - leads to the suggestion that contracts in Brazil should acknowledge this level of uncertainty by including explicit mortgage renegotiations within shorter periods.
Keywords: D15; G21; R31; 330; real estate; housing market; mortgage finance; decision-making; uncertainties